Peran Guru PAI dalam Meningkatkan Kecerdasan Spiritual Siswa melalui Penguatan Relasi Vertikal Dengan Allah SWT - Nst, Tini Melinda; Kustati, Martin; Amelia, Rezki; Gusmirawati, Gusmirawati (Lembaga Yasin AlSys, 2024)
This study aims to understand the role of Islamic Religious Education (PAI) teachers at SMP Negeri 05 Sinunukan in improving students' spiritual intelligence through strengthening vertical relationships with Allah SWT. The method used was descriptive qualitative with data collection techniques in the form of semi-structured interviews, direct observation, and documentation. Interviews were conducted with PAI teachers, students, principals, and school staff, while observations were made on religious activities such as getting students used to reading prayers and the Qur'an before starting learning Obliging and guiding students to pray zhuhur in congregation. Documentation involved collecting documents related to the PAI program. Data were analyzed by reduction, presentation, and verification of findings through data triangulation. The results showed that PAI teachers not only delivered religious materials but also acted as role models, integrating religious theory with real practices. Activities such as praying together and helping students apply religious values in everyday life by guiding students to pray zhuhur in congregation. And positive interactions between teachers and students. Students show improvement in their understanding and application of religious values, and feel the positive impact in their lives.